2014
DOI: 10.1111/1467-8462.12061
|View full text |Cite
|
Sign up to set email alerts
|

Aboriginal Disadvantage in Major Cities of New South Wales: Evidence for Holistic Policy Approaches

Abstract: Aboriginal Australians experience disadvantage relative to other Australians across multiple socioeconomic indicators. Whilst Aboriginal disadvantage occurs across the nation, its characteristics may differ between locations. This article presents the first econometric analysis of Aboriginal disadvantage in major cities of New South Wales. The analysis is based on a multiple indicator framework devised by the Productivity Commission, populated with data from the National Aboriginal and Torres Strait Islander S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Despite the continuing resilience of these cultures, Aboriginal and Torres Strait Islander people fare worse in terms of equity and opportunity than other Australians (AIHW, 2011). Although there is great diversity between and within language groups and disadvantage is not universal (Reeve & Bradford, 2014), it is the legacy of Australia's colonial history that, at the population level, Aboriginal and Torres Strait Islander people suffer greater levels of poverty, lower levels of educational attainment and higher rates of chronic disease, suicide, incarceration and violence than other Australians (AIHW, 2011). This stark difference in the quality of life culminates in a life expectancy for Aboriginal and Torres Strait Islander peoples that is more than 10 years shorter than for other Australians (AIHW, 2011) and is commonly referred to as ‘the gap’.…”
mentioning
confidence: 99%
“…Despite the continuing resilience of these cultures, Aboriginal and Torres Strait Islander people fare worse in terms of equity and opportunity than other Australians (AIHW, 2011). Although there is great diversity between and within language groups and disadvantage is not universal (Reeve & Bradford, 2014), it is the legacy of Australia's colonial history that, at the population level, Aboriginal and Torres Strait Islander people suffer greater levels of poverty, lower levels of educational attainment and higher rates of chronic disease, suicide, incarceration and violence than other Australians (AIHW, 2011). This stark difference in the quality of life culminates in a life expectancy for Aboriginal and Torres Strait Islander peoples that is more than 10 years shorter than for other Australians (AIHW, 2011) and is commonly referred to as ‘the gap’.…”
mentioning
confidence: 99%
“…However, evidence about the neighbourhood segregation of Indigenous peoples in cities is mixed, and they may also be at risk of being invisible within a larger population (Brand et al, 2016). Addressing this Indigenous disadvantage in cities requires integrated approaches to housing, social welfare, employment and training, entrepreneurship policies (Reeve and Bradford, 2014). There is also the possibility for cities to take a more active role in addressing Indigenous disadvantage with local partners and community representatives (OECD, 2018).…”
Section: Regional Policies Can Complement Structural Policies To Addrmentioning
confidence: 99%
“…139 A small number of population based studies including analysis of multiple social and cultural determinants involving Aboriginal and Torres Strait Islander peoples have been conducted at the international, national, or state level. [370][371][372][373][374][375] A small number of other studies have looked at one specific SCEDH such as racism 339,374 or housing. 341,376,377 At an international level, one longitudinal study based on Census data for Indigenous peoples from Canada, New Zealand, and Australia found that while small gains in social determinants like employment, education, and income were occurring, the relative gap with non-Indigenous peoples was rising in each country and was the worst in Australia.…”
Section: Strait Islander Communitiesmentioning
confidence: 99%
“…370 National and state level studies of Aboriginal and Torres Strait Islander peoples in urban areas found associations between social determinants like unemployment, low education attainment, and low socioeconomic status with health outcomes such as social exclusion and psychological functioning or distress. 372,374,375,378 Both a Western Australian study of social determinants in adolescents and a Victorian study of social determinants in adults did not measure racism, but identified experiences of racism as being an important component of future research involving social determinants. 375,378 These national and international studies are valuable overviews of a select number of broad social determinants operating in Aboriginal and Torres Strait Islander communities, but are missing many SCEDH important to Aboriginal and Torres Strait Islander peoples, and therefore the information they provide policy makers is incomplete and not community specific.…”
Section: Strait Islander Communitiesmentioning
confidence: 99%
See 1 more Smart Citation